Studi Fenomenologis Pernikahan Dini Dikalangan Santri Di Pondok Pesantren Wilayah Kecamatan Palengaan - Muchlis Muchlis (ASASI: Journal of Islamic Family Law, 2021)
Early marriage among santri is a social phenomenon in society. This early age is more about the age of education that is being undertaken. the practice for santri is different from that among young people who incidentally ended up in divorce on the basis of previous research. while the santri based on their religious beliefs are better able to defend it. This study uses qualitative research with a phenomenological study approach to reduce individual experiences of phenomena to a description of an essence by presenting primary data, namely the results of observations, interviews, and documentation. Early marriage among the students of Islamic boarding schools in the Palengaan sub-district, some are married and continue their education or choose to drop out of education, some are married to be the choice of students with the blessing of both parents and teachers. The factors are the will of parents, family, lack of parental education, their own will even because of economic limitations to continue to higher education. The impact of early marriage is positive and negative, but what dominates more is the negative impact, especially the social impact related to social relationships to become a complete family in the social structure and the psychological impact that makes mender to take part because of the immature mental, spiritual and so on. encouraged by the age of the students who are still early.